Heuristics Biases and Investment Decisions: The Mediating Role of Financial Literacy in the Nepalese Stock Market - Paudel, Sujan Raj; Shakya, Prasansha (Journal of Emerging Management Studies, 2025)
Purpose – Nepalese stock market is continuously emerging, with an increased number of investors every day. However, the investment mechanism of these investors differs, with some using a proper financial knowledge, while some investing just by rule of thumb. This paper examines the influence of heuristics bias on investment decisions and explore financial literacy as a mediator in the relationship between different heuristics biases and investment decisions. Design/ methodology/ approach – The sample for this study is taken as investors from the heart of Nepal, the capital Kathmandu Valley. This research uses a descriptive and causal study design and a convenience sampling technique to gather data from 228 respondents. A five-point Likert scale was used to collect the data. To assess the hypotheses, correlation, regression analysis, and Hayes’ Process Macro were used. The collected data were analyzed using SPSS. Findings and Conclusions – The study shows that overconfidence bias and anchoring bias has statistically significant relationships and are good predictors of investment behavior. Likewise, financial literacy partially mediates through different heuristics bias and investment decisions. This shows that heuristics shortcuts improve investment decisions when combined with financial literacy. Implications – The study is valuable for emerging investors aiming to grow their investments with very little knowledge about the stock market and invest based on hunches or ideas from social circles. The study strongly emphasizes investors to have knowledge about financial terminologies, concepts, numbers and figures rather than blindly investing in stock markets and equities. Originality/value – The findings of the study help with behavioral finance by examining anchoring biases, availability, representativeness, and overconfidence. The study illustrates how financial education might lessen illogical investing practices. Its conclusions encourage wise decision-making in Nepal’s financial sector by providing insightful information for investors, legislators, and educators.